Clinical Significance of Hypophosphatasemia in Children - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (SPRINGER, 2020)
Low serum alkaline phosphatase (sALP)-hypophosphatasemia-is a characteristic of hypophosphatasia (HPP), but related to several clinical conditions. Here, we evaluated the frequency, persistency and the etiology of hypophosphatasemia in children. In retrospective analyses of sALP measurements from children, evaluated according to in-house constructed age- and sex-specific reference ranges, patients with no normal sALP measurement (Unresolved hypophosphatasemia) were invited for reanalysis. Prospectively, ALP substrates, pyridoxal-5-phosphate (PLP), and phosphoethanolamine (PEA) were measured in patients with persistent hypophosphatasemia. Radiographs and ALPL gene sequencing for HPP were performed to the cases with elevated PEA and/or PLP. From 130,340 sALP measurements of 93,162 patients, hypophosphatasemia was detected in 1404 samples from 867 patients (0.9%). Among them, 745 had at least one normal sALP values in laboratory records, grouped as transient hypophosphatasemia. 75 out of 122 patients with unresolved hypophosphatasemia could be reanalyzed for sALP, of whom PLP and PEA measurements were required in 37 due to persistent hypophosphatasemia. Both PEA and PLP were elevated in 4 patients, and ALPL gene analysis showed heterozygous mutations in 3 patients and homozygous in 1 patient. Elevated PEA with normal PLP were detected in 3 patients, and one had a heterozygous ALPL mutation. Anemia was the most common diagnosis, and upper respiratory tract infections and chronic diseases were more common in transient and unresolved hypophosphatasemia, respectively. In conclusion, reflected persistent hypophosphatasemia frequency was 1/1552 (0.06%) in this large pediatric cohort and, ALPL gene mutations were detected in 13.5% (5/37) of the studied cases. Although biochemical hypophosphatasemia is not uncommon, clinically significant HPP is rare.
Keywords: Bone; Alkaline phosphatase; Reference ranges; Transient hypophosphatasemia; Persistent hypophosphatasemia; Hypophosphatasia; ALKALINE-PHOSPHATASE LEVELS; INFANTILE HYPOPHOSPHATASIA; VALIDATION; CHILDHOOD; DIAGNOSIS; ADULTS